Development of a dataset on the in-plane experimental response of URM piers with bricks and blocks. (30th November 2018) - Morandi, P.; Albanesi, L.; Graziotti, F.; Li Piani, T.; Penna, A.; Magenes, G.
Highlights: A dataset collecting the results of 188 in-plane cyclic tests on URM piers has been developed. Different masonry typologies constituted by bricks and blocks are included. A preliminary investigation on the in-plane lateral strength and displacement capacity has been performed. Some inconsistencies between code criteria and experimental evidence have been pointed out. The dataset provides a tool available for future studies on the in-plane response of URM piers. Abstract: In this paper, a dataset collecting the results of in-plane cyclic tests on unreinforced masonry piers, carried out within different research projects, is presented. The dataset includes brick and block walls with different materials, bed-and head-joint typologies, dimensions, boundary conditions and vertical applied loads. The development of such dataset aims at providing a tool for the improvement of the understanding and the evaluation of the main parameters that may influence and govern the lateral response of the URM piers under seismic excitation. A preliminary investigation on the in-plane lateral strength and displacement capacity, being two of the most significant parameters used in seismic analyses for the design and assessment of masonry buildings, has been proposed. The dataset, that already groups several specimens, is freely shared and might be continuously updated. This source of information of consistent and reliable test results represents a necessary step into the process of definition of shared rules within the scientific and technical community, in particular for the improvement of codified criteria, analytical and numerical models and testing procedures.